Infant Feeding Practices and Nutritional Status of Children of Less Than 1 Year (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective(s): To determine infant feeding practices along with the nutritional status of under 1 year children.Materials and Method: This descriptive type of cross sectional study was carried out in Department of Paediatrics of Shaheed Suhrawardy Medical College Hospital during the period from July to December 2012 on 52 admitted children of 29 days to 1 year of age.Results: Exclusive breastfeeding was found in 19 (86.4%) cases in under 6 months age group and 3 (10.0%) cases in more than 6 months age group. Complementary feeding with breastfeeding was found in 76% of more than 6 months old infant. Majority patients in both groups received breastfeeding >8 times / 24 hour. Ninety five percent infants of ? 6 months of age who were on exclusive breastfeeding and eighty three percent infants of > 6 months who were on breastfeeding plus complementary feeding were in normal nutritional status.Conclusion: Exclusive breastfeeding in infants upto 6 months of age and breastfeeding with complimentary feeding in more than 6 months of age provided better nutritional status.Bangladesh J Obstet Gynaecol, 2015; Vol. 30(2) : 74-79